90.4k views
5 votes
Please help me solve this!!!!1 ASAP

Please help me solve this!!!!1 ASAP-example-1
User Yashira
by
5.3k points

2 Answers

7 votes

Answer:

g(x) = - square root (x+8) reflected about the x axis and shifted 8 units to the left

h(x) = 2 square root x) +1 is enlarged by 2 in the y direction and shifted up 1 in the y direction

Step-by-step explanation: whabby not know whabby learn still.

User Mtrbean
by
5.0k points
1 vote

Answer:

g(x) = - sqrt(x+8) reflected about the x axis and shifted 8 units to the left

h(x) = 2 sqrt(x) +1 is stretched by 2 in the y direction and shifted up 1 in the y direction

Explanation:

y = f(x + C) C > 0 moves it left

So we moved it 8 units to the left

y = −f(x) Reflects it about x-axis

g(x) = - sqrt(x+8) reflected about the x axis and shifted 8 units to the left

y = f(x) + C C > 0 moves it up

so we moved it up 1 units

y = Cf(x) C > 1 stretches it in the y-direction

and stretched it by 2 in the y direction

h(x) = 2 sqrt(x) +1 is stretched by 2 in the y direction and shifted up 1 in the y direction

User Wahkuna
by
4.8k points